Revealing tumor cells and tissues with high selectivity through folic acid-targeted nanofluorescence probes responsive to acidic microenvironments - Li, Jing; He, Hongyi; Liu, Shuyan; Li, Xining; Wu, Fengfeng (Frontiers in Oncology, 2024)
Tumor-specific fluorescent probes must fulfill the dual requirements of targeted accumulation within tumors and high-resolution imaging capabilities. To achieve both tumor-targeted accumulation and high-resolution imaging performance, we developed a composite comprising an acid-responsive bodipy conjugated to amphiphilic PEG-b-PLA polymer, along with folic acid (FA)-modified PEG-b-PLA as a targeting moiety for active tumor-specific accumulation. Finally, a novel assembly of hybrid fluorescent nanoparticles was successfully synthesized by integrating these two components, demonstrating exceptional responsiveness to acidic conditions for fluorescence excitation and remarkable tumor-targeted accumulation capabilities. We conducted comprehensive in vitro and in vivo investigations employing techniques such as analysis of physicochemical properties, fluorescence-based probes detection at varying pH levels, assessment of in vitro cytotoxicity, evaluation of cellular uptake capacity, analysis of lysosomal co-localization imaging, examination of tumor fluorescence images in vivo, and investigation of biological distribution patterns. The results demonstrated that the acid-responsive nanofluorescence probe we designed and synthesized possesses desirable physical and chemical characteristics, including a small particle size and low cytotoxicity. Moreover, it exhibits rapid real-time response to acidic environments and displays enhanced fluorescence intensity, enabling the real-time tracking of probe entry into tumor cells as well as intracellular lysozyme accumulation. We achieved highly specific in vivo tumor visualization by combining nanoprobes targeting folate receptor. Through imaging cervical tumor mice, we demonstrated the precise imaging performance and high targeted accumulation of FA-targeted nanofluorescence probes in tumor tissue. Furthermore, we confirmed the in vivo safety of the FA-targeted nanofluorescence probe through biological distribution analysis. These findings highlight the potential widespread application of FA-targeted acid-responsive nanofluorescence probes for selective imaging of tumor cells and tissues.